(untitled) (Environmental Smoke, 2021)
The Institute for the Conservation of Nature and Forests (ICNF) has recently carried out work on planning and management of recreational fishing in the area of ​​the Mouro River drainage basin — a mountain watercourse in the North of Portugal (River Hydrographic Basin). Minho) which is born near the place of Lagarto (Lamas de Mouro, Melgaço), in the Peneda-Gerês National Park (PNPG). The model adopted was initially implemented (2008) to manage that activity in the Olo river basin (BH of the Douro river), and this methodology also served as a foundation for creating in 2020 in the Northeast region of Trás-os-Montes (Mente rivers, Rabaçal and Tuela – Vinhais and Bragança) plus three recreational fishing areas. In this context, 13 sampling stations were set up (12 in the Mouro river and 1 in the Sucrasto river), considered representative of a large part of the habitats that make up this study area, where actions were carried out to monitor the ichthyofauna (electrical fishing) and hydromorphological characterization of habitats (River Habitat Survey, RHS). The monitoring of benthic macroinvertebrates was an additional action, recently introduced in this type of work, aimed at improving the biological assessment of water quality and aquatic ecosystems and which is serving as a basis for the preparation of a Master’s Thesis. With this study, data was analyzed concerning age, growth, physical condition of the monitored specimens, as well as their relationship with the different types of habitats where they were captured. To detect spatial distribution patterns underlying biotic (species/abundance and species/ages) and environmental data, multivariate methods can be used. As a result of this work, the Ludic Fishing Zone (ZPL) of the Mouro River (and its tributaries) will be created, with the aim of promoting recreational and sport fishing based on more conservationist principles. With this initiative, ICNF intends to guarantee greater protection and sustainability of endogenous aquaculture resources, with particular emphasis on the case of Atlantic salmon (Salmo salar). This salmonid annually elects a significant part of these continental waters to complete its reproductive phase. However, other studies, in this context, should be developed to better understand the ecology of the species in a country that coincides with its southern limit of distribution in Europe.